Analisis Kemampuan Pemahaman Matematis Ditinjau dari Self-Regulated Learning - Jusra, Hella; Liddini, Uswatun Hasanah (Edumatica : Jurnal Pendidikan Matematika, 2022)
The purpose of this study is to analyze the ability of mathematical understanding in terms of Self-Regulated Learning. This is based on students who have not been able to independently identify, recognize, detail and arrange several questions that will arise in the problem. This research is a qualitative research with a descriptive approach, the subjects in this study were students of class X SMA Negeri in Jakarta. Based on the results of research that has been done, it is stated that students have three categories of Self-Regulated Learning, namely high, medium and low. Each question states an indicator of mathematical understanding ability, but only the high Self-Regulated Learning category fulfills all indicators of mathematical understanding ability. Because subjects with high Self-Regulated Learning category can understand all the questions that have been asked. Meanwhile, for students in the moderate Self-Regulated Learning category, they fulfill two indicators, namely; (1) students can define a concept in writing, (2) students can present a concept in a problem and turn it into another form of expression. For the low Self-Regulated Learning category, students do not meet two indicators of mathematical understanding ability, only meet one indicator, namely; can identify problems and determine the outcome of a problem.